PENGARUH PENAMBAHAN BERBAGAI SUMBER KARBOHIDRAT PADA PENGENCER SKIM KUNING TELUR TERHADAP KUALITAS SEMEN BEKU SAPI BALI - Ajrul Mukminat; Sri Suharyati; Siswanto . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
The aim of this research was to know kind of carbohydrate as energy sources in skim egg yolkextender. This study was conducted on April 11th –18 th 2014 at Regional Technical Service Unit-Regional Artificial Insemination Office Lampung, Terbanggi Besar District, Central LampungRegency, Lampung Province.The Completely Randomized Design (CRD) was used in these researchwith three treatments and three repetitions. The treatment consist of P1 (glucose supplementation 2%),P2 ( fructose supplementation 2%) and P3 (sucrose supplementation 2%). The data obtained wasanalyzed by using variance analysis 5%.Results of this research showed that there was no significantly (P>0.05) between provision of glucose,fructose although sucrose that added in each skim egg yolk extender towards the motility of spermcells and life percentage.